Graphic design, referenced : a visual guide to the language, applications, and history of graphic design - Gomez-Palacio, Bryony (Rockport Publishers, 2009)
"Graphic Design, Referenced" is a visual and informational guide to the most commonly referenced terms, historical moments, landmark projects, and influential practitioners in the field of graphic design. With more than 2,000 design projects illustrating more than 400 entries, it provides an intense overview of the varied elements that make up the graphic design profession through a unique set of chapters: principles - defines the very basic foundation of what constitutes graphic design to establish the language, terms, and concepts that govern what we do and how we do it, covering layout, typography, and printing terms; knowledge - explores the most influential sources through which we learn about graphic design; representatives - gathers the designers who over the years who have steered the course of graphic design in one way or another; and, practice - highlights some of the most iconic work produced